Wkład uzdolnionych jednostek i zachowań niekonformistycznych w cnoty w sferze publicznej - Gierczyk , Marcin (Studia Edukacyjne, 2018)
Giftedness and nonconformist behaviour have become a source of great interest in both the public sphere and in educational research. This is related to the fact that nonconformity (as a personality and character trait) has been, and still is, an indispensable element of the creative transformation of societies in the public sphere.1 The paper presents results of research conducted in the years 2014-2016 on the level of nonconformity of gifted students in Poland and England. The research, conducted with the Creative Behaviour Questionnaire III (CBQ III), was undertaken among 30 purposefully selected students from the University of Silesia (Poland) as well as Oxford University (England). By considering both the influence of nonconformists on the transformations taking place in the public sphere, and also the results of my research, I will examine whether nonconformity is a potential source of strength or weakness to the public sphere. In this context nonconformist is a person who does not conform to a generally accepted pattern of thought or action.